2020
DOI: 10.1177/2333721420935702
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Multicomponent Lower Extremity Training Technique on Physical Function in Healthy Older Adults: A Randomized Controlled Trial

Abstract: Objective: We aimed to examine the outcomes of our novel multicomponent lower extremity training (MLT) technique on physical function in older adults. Methods: Participants were randomly divided into a training group (TG) or a control group (CG). The TG (4 men, 14 women) received MLT for 24 weeks, once per week. MLT contains strength, balance, and flexibility components. The CG (5 men, 10 women) did not receive any training for 24 weeks. Nine lower extremity range of motions (ROMs; hip flexion, hip abduction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…Finally, because personality traits have been well documented as significant correlates of cognitive functioning, 39 mindfulness practice, 17 and self‐esteem 28 across adulthood, we also considered these variables as potential confounders in our analysis. We included the Big Five personality traits, comprising agreeableness (helpful, warm, caring, soft‐hearted, and sympathetic), conscientiousness (organized, responsible, hardworking, and careless [reverse coded]), extraversion (outgoing, friendly, lively, active, and talkative), openness (creative, imaginative, intelligent, curious, broadminded, sophisticated, and adventurous), and neuroticism (moody, worrying, nervous, and calm [reverse coded]) 40 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, because personality traits have been well documented as significant correlates of cognitive functioning, 39 mindfulness practice, 17 and self‐esteem 28 across adulthood, we also considered these variables as potential confounders in our analysis. We included the Big Five personality traits, comprising agreeableness (helpful, warm, caring, soft‐hearted, and sympathetic), conscientiousness (organized, responsible, hardworking, and careless [reverse coded]), extraversion (outgoing, friendly, lively, active, and talkative), openness (creative, imaginative, intelligent, curious, broadminded, sophisticated, and adventurous), and neuroticism (moody, worrying, nervous, and calm [reverse coded]) 40 .…”
Section: Methodsmentioning
confidence: 99%
“…16 Relatedly, mindfulness has been found to be associated with personality traits. For instance, Jung et al 17 found that mindfulness practice was associated with increased extraversion and openness and a decline in neuroticism in older adult participants. Further, it has been found that individuals who practiced meditation as a mindfulness intervention reported high self-esteem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ini dapat membuat lanjut usia lebih nyaman dalam bergerak dan berpartisipasi dalam aktivitas fisik. Latihan ROM sebaiknya disertai dengan latihan kekuatan otot dan keseimbangan untuk memberikan manfaat yang lebih komprehensif (Jung et al, 2020;Wu et al, 2011;Zarei et al, 2020). Konsultasi dengan profesional kesehatan atau fisioterapis dapat membantu merancang program latihan yang sesuai dengan kebutuhan individu lanjut usia.…”
Section: Pembahasanunclassified
“…Tai chi is a Chinese martial art focused on the balance between the practitioner’s slow movement and deep breathing, used for its meditative health benefits ( Carim-Todd et al, 2013 ; Hermanns et al, 2018 ). Pilates is another physical exercise method consisting of low-impact flexibility, postural balance, and muscular strength and endurance movements ( Jung et al, 2020 ; Kloubec, 2011 ) and focusing on positive thoughts, Pilates promotes mental clarity and reduces stress ( Lim & Park, 2019 ). All these movement therapies, as MBP, can be used primarily for managing the associated symptoms to improve the quality of life of persons with impaired cognitive functions ( Farhang et al, 2019 ; Zhang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%